Symbolic Interactionism Between Students and Caregivers in Pesantren - Fajri, Barlian; Abdulghani, Naser Ali (Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan Jawa Timur, 2025)
Amidst the current wave of modernization, challenges arise in preserving the traditional values that form the foundation of pesantren (Islamic boarding school) education. This study aims to examine how symbolic interactions between students and caregivers at the Pesantren Darullughah Wadda’wah (Dalwa) in Pasuruan contribute to the formation of the students' character and identity. Using a qualitative approach with descriptive-analytical methods, data were obtained through participant observation, in-depth interviews, and documentation. The results of the study indicate that symbolic interactions manifested through symbols such as the call